Aplikasi Pendataan Berita Acara Temuan Selisih Berbasis Web dengan Metode SWOT (PT Bank Negara Indonesia,Tbk) - Karno Diantoro; Fuadis Muhammad (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
In this modern era, the use of a multi-format system is still very much needed. Using a desktop-based application, this MIS program is packaged in a form that is easy for users to run. Research on this system to find out what is still a problem when the program is run. Based on this, the researcher analyzed the multiformat information system application system using the SWOT method through four factors, namely Strengths, Weaknesses, Opportunities, Threats. This model is used with the aim that a quality can be measured explicitly. The results of the research are able to solve the problems that exist at PT Bank Negara Indonesia, it becomeseasier to record discrepancies and the stored data is well maintained and can be easily searched.